Μελέτη γεωθερμικού συστήματος - Κοϊνάς, Ηρακλής (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
As the cost of energy continues to rise, the need to save energy and improve the overall energy efficiency of air conditioning systems becomes important. For this reason, the geothermal heat pump is becoming one of the most essential elements for energy savings in heating and cooling systems. Heat pumps achieve higher yields when they are coupled to ground heat exchangers (GHEs). There are two common types of GHEs the vertical and horizontal GHE. The present study models the horizontal GHEs, building on the already modeled vertical GHEs and adding new elements. The modeling is performed with the simulation software FlexPDE6.30 and describes the performance of horizontal GHEs when various characteristics change. The horizontal GHEs usually are buried at a depth of about 1-2 m with a series of tubes connected together. These exchangers are affected by seasonal weather conditions since they are placed in shallow ground in contrast to the vertical GHEs which usually are placed at a depth of up to 100 m. The modeled horizontal heat exchanger is constructed with four tube lines, 50 m in length each, embedded in three ground layers. The initial ground temperature matches a real case ground temperature in June at a certain location in Cyprus, with the top layer being at a higher temperature. Initially, we study the effect of diffusivity of the soil (through the use of different material layers) on the inlet and outlet temperature of the fluid flowing through the tubes of GHE. It is shown that values of diffusivity greater than 16x10-6 m² / s (critical value) do not decrease further the horizontal GHE temperature. Below this value, the effect of the diffusivity of the soil is very important, since the lower it is, the higher is the inlet and outlet temperature of the fluid flowing through the tubes of the horizontal GHE. Thereafter, by varying the center to center distance between the horizontal tubes of GHE it is observed that the inlet and outlet temperature of the fluid flowing through the tubes of the GHE, is not reduced further after a critical distance of 0.4 m. Then, we examine the depth that the solar heat can penetrate into the soil and how the performance of the horizontal GHE is affected. The calculated temperature of the ground during the course of a given day in a location in Cyprus (Prodromi), is then compared to measured values. Finally, conclusions are drawn.
Keywords: Geothermal Heat Pump; Heat Pumps; Γεωθερμική Αντλία Θερμότητας; Αντλίες Θερμότητας